John Selden : Measures of the Holy Commonwealth in Seventeenth-Century England. - Barbour, Reid (University of Toronto Press, 2003)
Engaging in style and substantive in analysis, Barbour's John Selden will add considerably to the limited body of work on this important seventeenth-century savant.